PENGARUH LOKASI DAN PROMOSI ONLINE TERHADAP KEPUASAN KONSUMEN PONDOK TELAGA IKAN DESA BANGUN SARI KECAMATAN BERINGIN KABUPATEN DELI SERDANG - Siti Khairunisa; Julianto, Julianto Hutasuhut; Anggia Sari Lubis; Adrial Falahi (Forum Kerjasama Pendidikan Tinggi, 2024)
The purpose of this research is to determine and analyze the influence of location andonline promotions on consumer satisfaction at Pondok Telaga Ikan Restaurant. The type of researchis quantitative. The population used in this research was consumers of Pondok Fish Lake. Thepopulation in this study was all consumers of Pondok Fish Pond in March. In this study, becausethe exact number of member populations is not known, the sample size was calculated using theCochran formula, so that in this study the sample was used. The research instrument uses aquestionnaire with a Likert scale data measurement scale. Data analysis techniques use validity,reliability and classical assumption tests. The data analysis method uses multiple linear regressionwith the help of the SPSS program. The research results prove that partially location has a positiveand significant effect on consumer satisfaction. Online promotions have a positive and significanteffect on consumer satisfaction. Simultaneously, location and online promotions have a positive andsignificant effect on consumer satisfaction at Pondok Telaga Ikan Restaurant. The adjustedcoefficient of determination (R Square) is 0.526, this means that 52.6% of the dependent variablecan be explained by the independent variable while the rest is explained by other variables outsidethe variables studied.